2011
DOI: 10.4028/www.scientific.net/kem.467-469.662
|View full text |Cite
|
Sign up to set email alerts
|

Getting Rid of the Wires: Curved Layer Fused Deposition Modeling in Conductive Polymer Additive Manufacturing

Abstract: Abstract. This paper describes an additive manufacturing technology that has the potential to print plastic components with integral conductive polymer electronic circuits. This could have a major impact in the fields of robotics and mechatronics as it has the potential to allow large wiring looms, often an issue with complex robotic systems, to be printed as an integral part of the products plastic shell. This paper describes the development of a novel Fused Deposition Modeling (FDM) process in which the laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Alayoldi, et al (2020) [68] investigated the effect of the infill pattern on the compressive strength of the part. It was found that triangular, grid and hexagonal infilled parts resulted in similar ultimate tensile strength (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72), while the quarter cubic infill exhibited a significantly lower strength of 27 MPa. It was also found that the grid pattern had the highest tensile strength due to its special layer arrangement in which the infill layers are crisscrossed one above the other as shown in Figure 5.…”
Section: Effect Of Infill Patternsmentioning
confidence: 99%
“…Alayoldi, et al (2020) [68] investigated the effect of the infill pattern on the compressive strength of the part. It was found that triangular, grid and hexagonal infilled parts resulted in similar ultimate tensile strength (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72), while the quarter cubic infill exhibited a significantly lower strength of 27 MPa. It was also found that the grid pattern had the highest tensile strength due to its special layer arrangement in which the infill layers are crisscrossed one above the other as shown in Figure 5.…”
Section: Effect Of Infill Patternsmentioning
confidence: 99%
“…Additive manufacturing generally involves extruding or deposition of material onto a flat horizontal surface and building up an object from numerous stacked planar layers. Relatively few papers have been published on the topic of Conformal Printing-examples include Curved Fused Deposition Modeling [1][2][3][4] or Direct Ink Writing onto curvilinear surfaces with a priori knowledge of substrate shape. 5 Recent publications describe deposition systems that can measure the shape and size of an unknown curved substrate and then immediately print on it in a repeatable accurate manner.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the electronics industry has been searching for new methods for manufacturing conductive lines in order to meet the requirements of smaller feature size, less environmental impact, less weight and volume, flexible electronics, embedded electronics, etc. Many new techniques have been developed during the past decade, such as Curved Layer Fused Deposition Modeling (CLFDM) [2], Laser-based Direct Write (LDW) [3], Laser Micro-cladding Electronic Pastes (LMCEP) [4], screen printing [5], offset lithography [6], aerosol jet [7,8], and inkjet deposition [9][10][11][12][13][14]. CLFDM is limited by the conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Fused deposition modeling (FDM) has become a prominent form of additive manufacturing and has been used to build mechanical structures for many commercial products. Although conductive polymers can be used in FDM to build conductive lines [2], the resistance is nonetheless too high for most of the applications. D. Espalin et al demonstrated a multi 3D system that can produce 3D, multi-material and multifunctional devices based on a combination of FDM process, direct printing technology, and a novel thermal embedding technology.…”
Section: Introductionmentioning
confidence: 99%